Developing a Content Model of a Mobile-Based Application to Manage Patients with Low-Back and Neck Pain - Yasaman Farjami Rad; Leila Shahmoradi; Noureddin Nakhostin Ansari; Scott Hasson; Maryam Ebrahimi; Meysam Rahmani Katigari (International Journal of Telemedicine and Applications)
Introduction. As a complementary tool in health, the design of mobile applications to influence care and increase awareness of patients has grown a lot. The purpose of this study is to design and validate the content model of a mobile-based application for managing patients with low-back and neck pain. Methods. This descriptive-analytical study was conducted in two main stages to determine the content model of the application. The first stage consisted of three steps: finding the right exercise, determining the right scale to assess the pain intensity, and determining the appropriate features of the application. In the second stage, data elements collected from the previous stage were prepared in the form of a questionnaire that was given to 12 experts in physical therapy and sports medicine for validation. After collecting the questionnaire, data elements in all parts were analyzed based on the content validity ratio (CVR) and descriptive statistics indicators. Result. The content of the application was prepared in the three axes of exercises for low-back and neck pain, assessment of pain intensity, and features of the application. In the axis of sports exercises, 8 exercises for back pain and 3 exercises for neck pain were included according to the reference books. A Functional Rating Index (FRI) scale with 10 elements was selected in the axis of determining pain intensity. Also, 12 features such as the daily exercise section, using the animation, and using an audio file to explain how to do exercises were included in the model. Conclusion. According to the gaps identified in the existing applications, determining the content model of the application that is based on evidence and according to the opinion of experts is useful in improving the apps. The content model of this study was presented in 3 axes to increase the patient’s willingness to do exercises, the correct way to perform exercises, conservative treatment, and check the progress of the treatment. The software developers can use these findings as a basis for designing new apps to manage low-back pain and neck pain.